ORGANIZATIONAL AND MARKETING SUPPORT AS A FACTOR IN THE DEVELOPMENT OF THE INNOVATIVE POTENTIAL OF LIGHT INDUSTRY ENTERPRISES - BERDYCHEVSKYI, Anton (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article It was concluded that innovative activity is a complex concept that combines the flow of the main and accompanying innovation processes with the aim of obtaining the final result - an innovative product. Achieving the appropriate result is possible under the condition of considering the innovation process as an integral (generalizing) phenomenon and applying a comprehensive approach to the management of the innovative potential of the enterprise. Summarizes the global changes that are taking place in social life and create challenges and obstacles for the development of entrepreneurship. Modern business structures try to adapt to a dynamic environment, ensure efficient work and activate innovative processes.The purpose of the article is to study the peculiarities of managing the entrepreneurial potential of business structures under the conditions of global challenges and the use of marketing tools in the formation of market business activity. The following methods were used for the research: systemic - for revealing the content of entrepreneurial potential, researching marketing tools and levers, specifying the place of marketing support in the management system of business structures; structural and logical analysis - to determine the features of modern trends in the development of entrepreneurial potential; graphic - for building a logical block diagram; logical generalization - to specify recommendations.The article defines the essence of entrepreneurial potential and the place of innovations and marketing tools in the management system of business structures. A logical block diagram of the formation of entrepreneurial business activity of business structures on the market is built. The peculiarities of modern structural problems of the light industry of Ukraine, regarding the formation of entrepreneurial potential, the development of innovative activity and the formation of marketing support for the management of business structures are analyzed.The article uses elements of scientific research aimed at more effective solutions to certain issues. For this, the information contained in various literary sources was collected and analyzed, its generalization was carried out, and conclusions and proposals were formulated. It has been established that a characteristic feature of managing business structures and their entrepreneurial potential with the use of marketing tools is that strategic management is formed not as a separate direction of the enterprise's activity, but as a short- or long-term business development plan. It was concluded that in today's conditions, one of the most progressive approaches to conducting a profitable business is the use of marketing tools in the management of business structures and their entrepreneurial potential.
Keywords: innovation; innovation potential; entrepreneurial potential; organizational and marketing support; ESG-business activity; European integration; management